The Effect Of Electronic Word Of Mouth And Digital Payment On Buying Intention In Hanan Boga Rasa Applications - Wandi Kurniadi (International Journal of Economics, Business and Innovation Research, 2023)
With technological advancements and information tomorrow, many business sectors use technology and media as a marketing tool. The current trend for long-term commercial performance is advertising evolution. However, issues arise when the company uses incorrect social networking platforms, which has a negative impact on the company. The goal of this study is to investigate the effect of electronic word of mouth and payment simplicity (digital payment) on purchase behavior in Tokopedia's Hanan Boga Rasa Applications business in Indonesia. In this study, 150 people were chosen at random to use an online shopping app on their smartphones. In this study, a multiple linear regression analysis strategy using SPSS software version 26 is used. The findings show that electronic word of mouth and digital payment have an excellent impact on purchase intent.